1975
DOI: 10.1002/j.1551-8833.1975.tb02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Dewatering and Its Physical Properties

Abstract: Discharging water‐treatment‐plant sludge into natural water courses is an unacceptable method of sludge disposal. The physical properties of sludge only add to the problem and increases the expense of tho complex process involved in rendering the sludge handleable. This article examines several methods of sludge dewatering and its ultimate disposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…The mass of the dry solids corresponded to the mass achieved after drying the test specimen in an oven at a temperature of 105±5 o C for a period of 24 hours. The geotechnical properties of some alum and iron-coagulant WTS materials have been report by Geuzens and Dieltjens (1991);Lim et al (2002); Novak and Calkins (1975); Raghu and Hsieh (1986);and Wang et al (1992). In particular, the permeability behaviour of an alum WTS was reported by Wang and Tseng (1993).…”
Section: Introductionmentioning
confidence: 80%
“…The mass of the dry solids corresponded to the mass achieved after drying the test specimen in an oven at a temperature of 105±5 o C for a period of 24 hours. The geotechnical properties of some alum and iron-coagulant WTS materials have been report by Geuzens and Dieltjens (1991);Lim et al (2002); Novak and Calkins (1975); Raghu and Hsieh (1986);and Wang et al (1992). In particular, the permeability behaviour of an alum WTS was reported by Wang and Tseng (1993).…”
Section: Introductionmentioning
confidence: 80%
“…However, in practice, the 300% maximum water content requirement is generally not a reliable guide for achieving minimum shear strengths necessary for landfilling. For instance, O'Kelly and Quille (2010) reviewed undrained strength against water content data presented for different alum WTR materials by Novak and Calkins (1975), Wang et al (1992), Wichmann and Riehl (1997) and O'Kelly (2008a). They found that the undrained strength of these materials ranged 6-80 kPa at 300% water content.…”
Section: Geotechnical Considerations For Landfilling Routementioning
confidence: 99%
“…However, no universal relationship exists for soils between the water content and undrained shear strength, which is used to calculate the shortterm factor of safety against geotechnical instability, since the shear strength is also dependent on a range of other factors, including natural differences in the composition of the suspended solids in the source water (effects mineralogy and organic content), the different types of treatments and amounts of chemicals used to separate the residue by-product at the municipal works, the test method, and the degree of specimen saturation. For example, a review of the literature (Novak and Calkins, 1975;Wang et al, 1992;Wichmann and Riehl, 1997) indicates that, at 300% water content, the undrained shear strength of alum WTRs can range between 6 and 80 kPa (Figure 12), although the amounts of chemicals in the residues tested by other researchers were not reported. However, the measured undrained shear strengths of the three alum WTRs tested in this study were more consistent (s u ¼ 40-80 kPa), since the source waters, treatment processes and amounts of chemical additives were comparable.…”
Section: Residue Dewatering and Landfill Disposalmentioning
confidence: 99%
“…The water content (w) is defined as the ratio of the mass of the pore water to the mass of the dry solids, expressed as a percentage. The mass of the dry solids is measured after ovendrying the test specimen at 105 AE 58C for a period of 24 h. Table 1 lists some engineering properties of alum WTRs reported in the literature (Lim et al, 2002;Novak and Calkins, Figure 1 shows undrained shear strength against water content data determined using the fall-cone penetrometer (Wang et al, 1992), miniature laboratory vane (Novak and Calkins, 1975;Wichmann and Riehl, 1997) and triaxial compression (O'Kelly, 2006) apparatus for alum and iron WTRs, as well as municipal sewage sludge, the latter a by-product of wastewater treatment processes. The geoengineering properties of sewage sludge are similar in many respects to those of WTRs, and extensive research on the shear strength behaviour of sewage sludge has been reported by O'Kelly (2004O'Kelly ( , 2005aO'Kelly ( , 2005bO'Kelly ( , 2005cO'Kelly ( , 2006.…”
Section: Introductionmentioning
confidence: 99%